1999
DOI: 10.1053/ejvs.1999.0852
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus as a Risk Factor for Early Outcome After Carotid Endarterectomy – a Population-based Studyf1

Abstract: diabetics had both a higher 30-day and 1-year mortality after CEA compared to non-diabetics, mainly because of cardiac complications. However, postoperative neurologic morbidity did not differ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 4 publications
0
22
0
2
Order By: Relevance
“…Several studies have shown that patients with diabetes present higher incidence of death and cardiovascular complications when undergoing endarterectomy [13,15]. Diabetes has been described by multiple authors [3,13,16,17,18] as a factor significantly affecting the results of CEA, but others have reported conflicting results [19,20,21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that patients with diabetes present higher incidence of death and cardiovascular complications when undergoing endarterectomy [13,15]. Diabetes has been described by multiple authors [3,13,16,17,18] as a factor significantly affecting the results of CEA, but others have reported conflicting results [19,20,21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…4 On the contrary, in another study, patients with diabetes had higher cardiac-related mortality, but there was no significant difference between the two groups of patients in neurologic postoperative morbidity. 3 Few studies have analysed the influence of DM on outcomes among patients who underwent CAS. A pooled analysis of outcomes from 2196 procedures found no higher perioperative risk of major adverse cardiac events in patients with diabetes who underwent CAS procedure.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In addition, stroke in patients with diabetes is associated with a worse functional outcome and higher mortality compared to their counterparts. 3 There is conflicting evidence on the effect of DM on the outcomes of patients undergoing carotid endarterectomy (CEA). A number of studies reported increased perioperative risk of stroke and death in patients with diabetes undergoing surgery, 4,5 and in some series, it was a marker of coronary insufficiency and a predictor of cardiac adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…4. A case -control study nested in the cohort of a national registry is an appropriate method to study complications and other adverse events after vascular surgery [26].…”
Section: The Utility Of a Vascular Registrymentioning
confidence: 99%
“…In-depth analysis of specific patient groups. We have validated the registry for femoropopliteal reconstructions [14], adverse events after chronic leg ischaemia [17,20], amputations [21,25], complications after carotid surgery [26,27], colonic ischaemia after aortoiliac surgery [22,23], mesenteric revascularisation [28] and reoperations in general [24]. Triangular inspections where hospital A inspects hospital B which inspects hospital C which inspects hospital A.…”
Section: B1 How Do We Address Validity?mentioning
confidence: 99%